Research hotspots and frontiers about role of visual perception in stroke: A bibliometric study - Zhang, Nannan; Li, Chong; Chen, Jianmin; Liu, Xiahua; Wang, Zhiyong; Ni, Jun (Frontiers in Neurology, 2022)
Background: Visual perception is a dynamic process of perceiving the environment through sensory input and transforming sensory input into meaningful concepts related to environmental visual knowledge. Many studies focusing on the role of visual perception after stroke have been published in various journals. However, a bibliometric analysis in the domain of visual perception after stroke is still lacking. This study aimed to deliver a visual analysis to analyze the global trends in research on the role of visual perception after stroke in the last 10 years. Methods: The literature was derived from the Web of Science core collection database from 2012 to 2021. The collected material was limited to English articles and reviews. CiteSpace and Microsoft Excel were used for bibliographic analysis. Results: A total of 298 articles were included in the analysis. The annual number of publications increased from 23 to 42 in the last decade. Rehabilitation was the main research hotspot (n=85). Journal of Physical Therapy Science published the largest number of papers (n=14). The most influential author, institution, and country was Rowe FJ (n=17), League of European Research Universities (n=45), and England (n=54), respectively. The keywords with the longest burst period are field defect, hemineglect, disorder, and quality of life. Conclusion: This study analyzes the papers on the role of visual perception after stroke in the past 10 years and provides a new perspective for research in this field. At present, the number of articles in this field is not large and the cooperation network is not close enough. In the future, it is necessary to strengthen the cooperation among various countries, institutions, and authors. In addition, large samples, and randomized controlled trials are needed to identify the potential treatments and pathophysiology for visual perceptual impairment after stroke.